Repetition in Simultaneous Interpreting of Political Discourse: Obama's Speech in Cairo - Abu Assi, Hani Mohamed Ali (2011)
A Master of Arts Thesis in Translation and Interpreting (English/Arabic/English) by Hani Mohamed Ali Abu Assi Entitled, "Repetition in Simultaneous Interpreting of Political Discourse: Obama's Speech in Cairo," submitted in June 2011. Available are both hard and soft copies of the thesis.